Efektivitas Residu Insektisida Actellic 500EC pada Berbagai Macam Permukaan Dinding Terhadap Kematian Nyamuk Anopheles aconitus, Aedes aegypti, dan Culex quinquefasciatus - Boesri, Hasan; Susanti, Lulus (Lembaga Penelitian Universitas YARSI, 2008)
Insecticide spray has been commonly practiced for malaria eradication program. Well chosen and accurate dose of insecticide is required to obtain the best result. In this study, a small scaletrial of Actellic 500EC residual spray with dosage ranges of 1.0 ml/m2, 2.0 ml/m2, 4.0 ml/m2 and 5.0 ml/m was applied on wall, shelf and bamboo surfaces. Three malaria vectors e.g. Anopheles aconitus, Aedes aegypti, andCulex quinquefasciatus mosquitoes, 3-4 days old and well fed were used for the experiment using bioassay test kit cone (WHO standard 1975). The result showed that 4.0 ml/m dosages of Actellic 500EC were more effective than the other dosages. The mosquito mortality was 100% in one week for An. aconitus, Ae. aegypti and Cx. quinquefasciatus.